Altered Resting-State Functional Activity in Patients With Autism Spectrum Disorder: A Quantitative Meta-Analysis - Wang, Wenhui; Liu, Jia; Shi, Shaojie; Liu, Taiyuan; Ma, Lun; Ma, Xiaoyue; Tian, Jie; Gong, Qiyong; Wang, Meiyun (Frontiers in Neurology, 2018)
Background: There is accumulating evidence showing that autism spectrum disorder (ASD) patients have obvious changes in resting-state functional brain activity. So far, there has been no meta-analyses of the resting-state brain activity alterations in ASD patients. We attempted to explore the resting-state functional activity changes in ASD patients, possibly providing a new perspective for investigating the pathophysiology of ASD patients. Methods: We screened relevant studies published before August 2017 in PubMed, Ovid, Web of Science, China National Knowledge Infrastructure (CNKI) and the Wan-fang database. Fifteen resting-state functional neural activity datasets (including 382 patients and 348 healthy controls) were included. Through the use of the effect-size signed differential mapping (ES-SDM) method, we carried out a meta-analysis of resting-state functional activity studies of ASD patients. Results: Compared with healthy controls, ASD patients showed hyperactivity in the right supplementary motor area, middle frontal gyrus, inferior frontal gyrus, the left precentral gyrus, and the bilateral cerebellum hemispheric lobule (VIII/IX) and hypoactivity in the right middle temporal gyrus, superior temporal gyrus, and the left precuneus, posterior cingulate cortex, median cingulate cortex and bilateral cerebellum (crus I). Conclusion: This meta-analysis indicates that ASD patients have significant and robust resting-state brain activity alterations in the language comprehension network, inferior-posterior cerebellum, default mode network (DMN) and cerebellar crus I. These brain regions may serve as specific regions of interest for further studies of ASD, which will allow us to further clarify the neurobiological mechanisms in ASD patients.